Chemical Composition and Antibacterial and Antioxidant Activities of Stem Bark Essential Oil and Extracts of Solanecio gigas - Mequanint Molla Yitayeh; Amanu Monie Wassihun (Biochemistry Research International)
Herbal medication developed from natural resources has to have antibacterial and antioxidant effects. The aim of this research is to look at the chemical makeup of Solanecio gigas (S. gigas) stem bark essential oil (EO), as well as the effectiveness of EO and extracts (chloroform, ethyl acetate, and methanol) against human pathogenic bacteria and their antioxidant activity. The GC-MS analysis identified 23 components, accounting for 98.7% of the total oil containing Methylene chloride (49.2%), sabinene (10.5%), 1-nonene (11.3%), Terpinen-4-ol (6.9%), Camphene (4.3%), γ-terpinene (3.6%), α-phellandrene (2.9%) β-myrcene (2.6%), 1,2,5-Oxadiazol-3-carboxamide, 4,4′-azobis-2,2′-dioxide (2.4%), α-terpinene (1.9%), 1-Octanamine, N-methyl- (1.9%), ρ-cymene (1.6%) as major components. The antibacterial efficacy of the EO and extracts (25, 50, 100, and 200 mg/ml) was demonstrated by the inhibitory zones (8.5 ± 0.47–23.3 ± 0.36 and 7.2 ± 0.25–22.0 ± 0.45 mm), respectively. The MIC values of the extracts and the EO were 120–150 and 240 to <1100 μg/ml, respectively. The EO also demonstrated a significant antibacterial impact. The EO and methanolic extract had free radical scavenging activities with IC50 value, 13.8 ± 0.48 and 4.2 ± 0.04 μg/ml, respectively. In comparison to the other extracts, the methanolic extract had the greatest phenolics (100.2 ± 0.13 μg GAE/mg of dry extract) and flavonoid contents (112.1 ± 0.18 μg CE/mg of dry extract).